2021
DOI: 10.1002/ett.4326
|View full text |Cite
|
Sign up to set email alerts
|

A fog‐based fault‐tolerant and QoE‐aware service composition in smart cities

Abstract: Nowadays, the smart city trend has attracted an important number of municipalities, enabling to control and manage smartly the city environment and provide the citizens with value‐added urban services. In this regard, Internet of Things and fog computing play a key role in providing smart city services, simplifying the decision making for city authorities and improving the quality of experience (QoE) for citizens. In this article, we address the problem of selecting appropriate urban service providers and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The authors in [ 22 ] have proposed a fault-tolerant architecture for service composition in a smart cities environment adopting fog computing technology. The proposed method is able to handle service composition problem via RESTful IoT technology.…”
Section: Related Workmentioning
confidence: 99%
“…The authors in [ 22 ] have proposed a fault-tolerant architecture for service composition in a smart cities environment adopting fog computing technology. The proposed method is able to handle service composition problem via RESTful IoT technology.…”
Section: Related Workmentioning
confidence: 99%
“…Parameters that an optimal placement strategy must keep in mind are latency, reducing the energy consumption, minimize the cost and response time. 20,21 There are many existing works related to service placement in cloud/fog computing. Rahman et al 7 sum up and outline the architecture of the fog computing model, functionality, related paradigms, security challenges, and various real-time applications such as smart grid, traffic control and increased reality.…”
Section: Related Workmentioning
confidence: 99%
“…Recent research works have revealed the significance and pertinence of fog computing. 20 However, in terms of implementation view, most of the works have not bestowed up on the technical aspect of the paradigm.…”
Section: Related Workmentioning
confidence: 99%
“…Over recent years, the Internet of Things (IoT) has been integrated in our daily lives, which make the use of IoT applications (access control or face recognition for instance) in the context of smart city [1,2], smart healthcare [3], smart home [4], etc., more and more popular. Fog computing paradigm, as an extension to cloud computing, plays a crucial role in executing the IoT applications.…”
Section: Introductionmentioning
confidence: 99%
“…The task scheduling process is performed in the fog layer closed to the end-user. 2 We use a classical formulation of task scheduling as an Integer Linear Programming (ILP) multi-objective optimization problem considering the selection of appropriate fog nodes under certain constraints with the aim of minimizing both task completion time and energy consumption as two QoS parameters in a fog computing system. To solve this optimization problem, we design a new approach called OppoCWOA, which is a combination of WOA, Opposition-based learning, and Chaos theory.…”
Section: Introductionmentioning
confidence: 99%